Exploring Public Health Arabic Vocabulary For Arabic Teaching Materials - Moh. Buny Andaru Bahy; Kamal Yusuf; Ahmad Dzulkifli Rif'at (Institut Agama Islam Negeri (IAIN) Metro, 2022)
The emergence of new vocabulary related to public health is very important for the public to know, especially the new vocabulary about the Covid-19 pandemic in Arabic. This study aims to promote Arabic vocabulary - based teaching materials related to public health to introduce Arabic learners to new vocabulary. This study uses a descriptive qualitative approach based on library research by using the steps of preparing teaching materials using the Dick and Carey model. The data for this research is sourced from the online electronic media of the BBC Arabic, using vocabulary adaptation techniques to compile Arabic teaching materials. The results of this study confirm that in the preparation of Arabic teaching materials, the four basic principles of fhe foreign language learning approach are used. Based on the research that has been carried out, it was found that there are several of new vocabularies related to the Covid-19 pandemic in Arabic. Furthermore, the adaptation of the development of new Arabic vocabulary teaching materials is arranged according to the principles and concepts of language learning, so that in the implementation and teaching of new vocabulary students are expected to achieve maximum results.